Western frontier of Poland : documents, statements, opinions - Lesniewski, Andrzej (Warsaw Warsaw : Polish Institute of International Affairs Western Press Agency, 1965)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: territoriale kwesties; Polen